Analyzing the Impact of Social Media on Business Development Eiser Florist Case Study - Nazlaturrohmah; Pasaribu, Veta Lidya Delimah (Indonesian Journal of Entrepreneurship and Startups, 2025)
In today's ever-evolving digital era, social media has become one of the most influential tools in various aspects of life, including in the field of entrepreneurship. Social media not only functions as a means of communication and social interaction, but also plays an important role in marketing activities, building brands (branding), and business development. This study aims to examine in depth the role of social media in supporting business growth. The methods used include literature studies by analyzing various scientific references such as journals, books, and other trusted sources related to the use of social media in business development, as well as direct interviews with business owners. The results of the study revealed that the effective use of social media, especially through the creation of creative content, contributed greatly to increasing sales figures. A case study on Esier Florist shows that they have succeeded in utilizing digital media to strengthen their brand and build closeness with consumers. The strategies implemented include: building an existence on social media platforms, using storytelling techniques to form a brand identity for example by conveying the story behind the establishment of a flower bouquet business, the quality of the materials used, and the values upheld in each product. This approach helps create an emotional bond with customers. In addition, Esier Florist also actively analyzes data and input from consumers to continuously improve their services and products